Implementing online patient feedback in a 'special measures' acute hospital: A case study using Normalisation Process Theory. (April 2021) - Baines, Rebecca; Underwood, Frazer; O'Keeffe, Kim; Saunders, Jessica; Jones, Ray B
Objective: Online patient feedback is becoming increasingly prevalent on an international scale. However, limited research has explored how healthcare organisations implement such feedback. This research sought to explore how an acute hospital, recently placed into 'special measures' by a regulatory body implemented online feedback to support its improvement journey. Methods: Semi-structured interviews were conducted with eleven key stakeholders involved in the implementation and/or use of online patient feedback. Data was analysed using deductive thematic analysis with Normalisation Process Theory used as the analytical framework. Research findings are translated into the Engage, Support and Promote (ESP) model, a model of rapid feedback adoption. Results: Participants viewed the implementation of online feedback as an opportunity to learn, change and improve. Factors found to facilitate implementation were often linked to engagement, support and promotion. Although less frequently described, barriers to implementation included staff anxieties about time pressures, moderation processes and responding responsibilities. Such anxieties were often addressed by activities including the provision of evidence based responder training. Overall, staff were overwhelmingly positive about the value of online feedback with 24 impacts identified at an individual and organisational level, including the ability to boost staff morale, resilience and pride. Conclusions: The rapid implementation of online patient feedback can be achieved in a 'special measures' organisation. However, the difficulties of implementing such feedback should not be underestimated. In order to embed online feedback, staff members need to be engaged and feel supported, with opportunities to provide, respond and invite patient feedback frequently promoted to both patients and staff members.